Parental criticism and adolescent internalising symptoms: using a Children‐of‐Twins design with power calculations to account for genetic influence. (10th August 2021) - Ahmadzadeh, Yasmin I.; Eley, Thalia C.; Hannigan, Laurie; Creswell, Cathy; Lichtenstein, Paul; Spotts, Erica; Ganiban, Jody; Neiderhiser, Jenae; Rijsdijk, Fruhling; McAdams, Tom A.
Abstract : Background: Parental criticism is correlated with internalising symptoms in adolescent offspring. This correlation could in part reflect their genetic relatedness, if the same genes influence behaviours in both parents and offspring. We use a Children‐of‐Twins design to assess whether parent‐reported criticism and offspring internalising symptoms remain associated after controlling for shared genes. To aid interpretation of our results and those of previous Children‐of‐Twins studies, we examine statistical power for the detection of genetic effects and explore the direction of possible causal effects between generations. Methods: Data were drawn from two Swedish twin samples, comprising 876 adult twin pairs with adolescent offspring and 1, 030 adolescent twin pairs with parents. Parent reports of criticism towards their offspring were collected concurrently with parent and offspring reports of adolescent internalising symptoms. Children‐of‐Twins structural equation models were used to control for genetic influence on the intergenerational association between parental criticism and adolescent internalising. Results: Parental criticism was associated with adolescent internalising symptoms after controlling for genetic influence. No significant role was found for shared genes influencing phenotypes in both generations, although power analyses suggested that some genetic effects may have gone undetected. Models could not distinguish directionality for nongenetic, causal effects between generations. Conclusions: Parental criticism may be involved in psychosocial family processes in the context of adolescent internalising. Future studies should seek to identify these processes and provide clarity on the direction of potential causal effects.